Dimensi Rasional Dalam Pemikiran Muhammad Abduh 1849 – 1905 (Studi Bidang Pendidikan, Politik Dan Sosial-Keagamaan) - M Fadholi; Muhammad Aziz; Hery Purwanto (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, The dynamics of social reality, always gives rise to tensions which in the end not only creates challenges for Muslims (who care about the position of Islam vis-à-vis) in their social cultural reality, but also can create intellectual and social conflicts between Muslims whole. The progress of modern science and technology entered the Islamic world, which in Islamic history was seen as the beginning of the modern period. In this context, Islamic renewal has a logical consequence on critically reviewing and examining the existing Islamic understanding, both in the fields of culture and aqeedah, including Islamic education. Therefore, the idea of the Islamic thought reconstruction program also has its roots in the idea of the modernism of thought and Islamic institutions as a whole. In other words, the reconstruction of Islamic thought cannot be separated from the rise of Islamic modernism's ideas and programs. The presence of muhammad abduh in his thoughts is inseparable from the socio-historical that surrounds him. This paper is focused on discussing several things: 1) the history of the life of Muhammad Abduh, 2) the geology and style of his thought, 3) Muhammad Abduh's ideas of thought 4) The influence of Muhammad Abdu's thoughts in renewal.Keyword: Muhammad abduh, Islamic thought, classical-modern